Plant Gall Diversity in Burned Semi-natural Grasslands in Japan. Issue 1 (2nd February 2023) - Koyama, Asuka; Ide, Tatsuya
Abstract: We surveyed woody plants, including oaks and chestnuts ( Quercus L. and Castanea Mill.), and recorded the inhabiting galls induced by oak gall wasps (Hymenoptera: Cynipidae: Cynipini) at seven Japanese semi-natural grassland sites maintained by traditional regular burning with two of the seven abandoned grassland areas. Woody plants were established in all burned and abandoned grasslands. Oak species were found at four of the seven sites. In total, 15 types of cynipid galls were recorded at all four sites where oak species were found. However, the occurrence of species was site-specific for host trees and cynipid galls. Although a few ecological studies of oak gall wasps inhabiting grassland environments, which have rapidly decreased in recent decades, have been conducted, this study suggests that semi-natural grasslands may be potential habitats for oak gall wasps and their host trees, and we provide a checklist of oak gall wasps with host oak records in semi-natural grasslands throughout Japan.